Mappe di pericolosità e rischio idraulico nell’alluvione in Sicilia del 2018 - Gagliano, Filippo (GEOmedia, 2021)
Floods, as a major natural disaster, affect many parts of the world, not including developed countries. Due to this natural disaster, every year there are losses of human life and damage to the territory for millions of euros. Damage and losses can be prevented and limited by providing reliable information to institutions and citizens through flood hazard models and maps (Demir, 2015). Hydraulic models and digital cartography are essential for municipal planning, for civil protection emergency plans, for a correct design of works to prevent hydrogeological phenomena (Goodell and Warren, 2006). In the first days of November 2018, Sicily was affected by a phase of disturbed weather, characterized by intense and abundant rains that caused serious damage to the community and the territory. Geographical information systems (GIS) using spatial data are able to integrate hydraulic models for the simulation of flood events and are capable of drawing up maps of hydraulic hazard and estimating damage from hydrogeological instability (Demir, 2015). The GIS integrated with the hydraulic model is able to estimate the flood profile with a fixed return time. The hydraulic model used was developed after 1970 by the River Software Analysis System (HEC-RAS) hydrological engineering center of the United States Army Corps of Engineers (USACE), and is now widely used in Europe and America. GIS and HEC-RAS models have been successfully used to obtain flood maps of the Waller River in Texas (Tate et al., 2002), Ohio Swan River Basin (Wiles and Levine, 2002), Atrato River in Colombia (Mosquera-Machado and Ahmad, 2007), Vistula River in Warsaw, Poland (Gutry-Korycka et al., 2006), the Gordon River in France (Sheffer et al., 2008), northwestern Colombia (Mosquera-Machado and Ahmad, 2007), central-eastern Dhaka in Bangladesh (Masood and Takeuchi, 2012), and Onaville in Haiti (Heimhuber, 2015). Celik et al. analyzed the Kozdere Stream 2004 flood in Istanbul using HEC-RAS and GIS (Celik et al., 2012). Sole et al. they have drawn up risk maps of the Basilicata region (Italy), generating profiles of free-flowing currents for different return times (30, 200 and 500 years) (Sole et al., 2007). Masood and Takeuchi used HEC-RAS and GIS to assess flood danger, vulnerability and hydraulic risk in Middle East Dhaka (Masood and Takeuchi, 2012), obtaining flood maps for floods with a 100-year return time. Sarhadi et al. investigated forecasting models of flooding in rivers in southeastern Iran using HEC-RAS and GIS (Sarhadi et al., 2012). Heimhuber et al. they used HEC-RAS and GIS to perform the simulations in one-dimensional and non-stationary motion conditions for the design of the large Lan Couline channel (Heimhuber et al., 2015). The aim of this study is to study models to simulate scenarios for flood events in the Milicia River basin using the GIS and HEC-RAS for different return periods (50, 100 and 300).